Gender Differences in Saudi EFL Undergraduate Students’ Perceptions toward the Impact of Collaborative Writing - Alrayes, Layan Ali (Journal Corner of Education, Linguistics, and Literature, 2024)
Given the importance of collaborative writing, it has been generally investigated and discussed in different educational aspects. Gender difference is a factor that could contribute to the impact of collaborative writing. Therefore, the current study tried to illuminate the perceptions of gender differences among Saudi EFL undergraduate students regarding the effect of collaborative writing on written and social skills. Therefore, the study utilized an online survey adapted from previous studies and modified to fix the statements to the study's aims. The survey was distributed online  on Telegram via different channels, and (N = 74 Saudi undergraduate students) attending different universities in Saudi Arabia, with an equal number of 37 females and males, took part in the study. Furthermore, the independent sample t-test was used to analyze the data, and the results showed no statistically significant difference in the perceptions of both genders toward the impact of collaborative writing on both written and social development. These findings suggest further studies in this regard by employing more than one instrument to gain more in-depth data about how gender differences and cultural and educational background might impact the perceptions of students toward collaborative writing.